Controlling malaria in pregnancy: how far from the Abuja targets? (2016)
Background. The Roll Back Malaria (RBM) initiative recommended that all pregnant women receive Intermittent Preventive Treatment (IPTp) and that by 2010 at least 80% of people at risk of malaria (including pregnant women) use insecticide-treated bednets (ITN) in areas with stable transmission. We evaluated ITN/IPTp coverage, explored its associated factors, and estimated the number of pregnancies protected from malaria. Materials and methods. This analysis was based on data from the 2012 National HIV/AIDS and Reproductive Health Survey (NARHS Plus). To assess ITN coverage, we used the population of women that was pregnant (n=22,438) at the time of the survey. For IPTp coverage, we used women that had a live birth in the 5 years preceding the survey (n= 118,187) and extracted the population of pregnant women that, during their last pregnancy, received drugs for protection against malaria. We estimated the number of live births using the projected population of females in each state, population of women of child -bearing age and the total fertility rate. The estimated number of pregnancies covered/protected by ITN and IPTp was obtained from a product of the estimated live births and the reported coverage. Multivariate logistic regression was used to determine factors associated with ITN and IPTp use. Results. We estimated that there were 5,798,897 live births in Nigeria in 2012, of which 3,537,327 and 2,302,162 pregnancies were protected by ITN and IPTp, respectively. Four of 36 states achieved the 80% RBM target for ITN coverage. No state achieved the 100% target for IPTp. Education and socio-economic status were associated with IPTp use. Conclusion. ITN coverage was higher than in previous estimates even though it is still below the RBM targets. However, IPTp coverage remained low in 2012 and was not likely to increase to match the 2015 target coverage of 100%.